Socioeconomic Risk Factors for Celiac Disease Burden and Symptoms. Issue 4 (April 2016) - Oza, Sveta S.; Akbari, Mona; Kelly, Ciarán P.; Hansen, Joshua; Theethira, Thimmaiah; Tariq, Sohaib; Dennis, Melinda; Leffler, Daniel A.
Abstract : Background & Aims: Celiac disease (CD) affects approximately 1% of the population and negatively affects aspects of life including physical and social function. The relationship between socioeconomic (SE) factors, symptom severity, and perceived burden of living with CD is not well understood. The objective of this study was to assess the relationships between income, symptoms, and perceived burden of CD. Methods: In this survey study conducted at a tertiary care center, 773 patients 18 years of age or more with biopsy confirmed CD were eligible to participate. Patients completed a survey with information on SE data, the validated Celiac Symptom Index (CSI), and visual analog scales (VAS) assessing overall health, CD-related health, difficulty in following a gluten-free diet (GFD), and importance of following a GFD. Results: Three hundred forty one patients completed the survey. Higher income predicted better overall health, better CD related health, and fewer symptoms. In the logistic regression model, low income was associated with greater CD symptoms (odds ratio=6.04, P =0.002). Other factors associated with greater symptoms were younger age, poor overall health state, and more physician visits. Factors associated with increased burden of CD included hospitalizations, more symptoms, poor overall health state, and burden of following a GFD. Conclusions: Patients with lower incomes have worse CD-related health and greater symptoms. Those with low income had 6 times the odds of greater symptoms compared with those with high income. Our data suggest that income is associated with perceived overall health, CD-related health, and CD symptoms. Abstract : Supplemental Digital Content is available in the text.